Evaluation of Romania's potential for producing renewable energy from agriculture and forestry - Elena Şurcă (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
Renewable energy production is an alternative to traditional energy resources that are being depleted, these new resources will gradually replace the exhausting energies by combining the three main features of the present century, so that sustainable development, energy security and environmental protection become defining elements in terms of renewable energy production. The energy sector communicates and is closely linked to the economic sector, the defining resource with a major influence on the economy being oil, where its exhaustion and other natural energy resources would lead to economic and political instability, which is why it is necessary to highlight the possibility of substitution exhaustible resources through different sources of renewable energies: solar, wind, microhydro, geothermal and biomass. In view of the above, we will highlight Romania's potential in the production of renewable energy from biomass, the materials provided by the agricultural sector and the forestry sector, but also the energy consumption in agriculture and forestry, as well as the type of biofuel used (liquid or solid), which draws a parallel between the two categories of biofuels obtained from the same resource. We will also highlight Romania's position in the European Union in this field, highlighting the national and European objectives on this issue.
Keywords: Q23; Q42; 330; renewable energy; biomass; energy security